PENGARUH KUALITAS PRODUK DAN CITRA MEREK DALAM MENINGKATKAN LOYALITAS PELANGGAN - Sipayung, Helena Margaretha; Tjiptodjojo, Kartika Imasari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
A strong brand and a product with good quality will encourage a stronger desire for customers not to switch in purchasing. Apple products are products with a strong brand and quality that is recognized worldwide. This is what drives the purpose of the study to see how these two variables can affect customer loyalty. Data were collected through questionnaires distributed to 121 respondents who met the criteria, such as having used Apple products for more than a year. The results show that product quality and brand image simultaneously affect customer loyalty with a contribution of 61.8%.